Phylogenetic analysis of colubrid snakes based on 12S rDNA reveals distinct lineages of Dendrelaphis pictus (Gmelin, 1789) populations in Sumatra and Java - FITRA ARYA DWI NUGRAHA; FATCHIYAH FATCHIYAH; NIA KURNIAWAN; ERIC NELSON SMITH (Society for Indonesian Biodiversity, 2018)
Nugraha FAD, Fatchiyah F, Smith EN, Nia Kurniawan N. 2018. Phylogenetic analysis of colubrid snakes based on 12S rDNA reveals distinct lineages of Dendrelaphis pictus (Gmelin, 1789) populations in Sumatra and Java. Biodiversitas 19: 303-310. The phylogenetic relationship among the major colubrid snakes, particularly those of the subfamily Colubrinae, has been the subject of much debate. Also, there was limited data on the molecular relationships of Sundaland colubrid snakes. This study aimed to examine the relationships among colubrid snakes from Sumatra and Java based on fragments of 12S rDNA gene. We sequenced 17 specimens of colubrid snakes representing 5 genera and 2 subfamilies: Colubrinae and Ahaetullinae. We used maximum likelihood, maximum parsimony and Bayesian inference methods for inferring phylogenetic relationships. The result of our phylogenetic analyses is in line with the previous findings for the separation between Colubrinae and Ahaetullinae. Interestingly, we found two distinct clades of Dendrelaphis pictus species with the high genetic divergence between them where D. pictus from Sumatra and West Java separated from Central and East Java clade. Our divergence time estimation showed that the differentiation between these clades of D. pictus occurred in the late Miocene epoch (8.9 Ma) when Sumatra and Java separated after being inundated in the early Miocene epoch.